2019
DOI: 10.1002/ijc.32039
|View full text |Cite
|
Sign up to set email alerts
|

Dietary cadmium and risk of breast cancer subtypes defined by hormone receptor status: A prospective cohort study

Abstract: Diet is the primary source of cadmium-a proven Group 1 human carcinogen-for non-smokers. Observational studies investigating the effect of cadmium from food sources on breast cancer risk have produced inconsistent results. We examined the association between dietary cadmium and risk of breast cancer defined by estrogen receptor (ER), progesterone receptor (PR) and HER2 status, in 8924 women recruited to a prospective study between 1987 and 1992. Dietary cadmium intake was estimated using a semi-quantitative fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(21 citation statements)
references
References 43 publications
0
20
0
1
Order By: Relevance
“…In addition, we accounted for major established or putative risk factors such as body weight, smoking habits, hormone replacement therapy/oral contraceptive use, and partially lack of physical activity, and alcohol intake (64-67) by using the most adjusted estimates from included studies. However, we acknowledge that unmeasured confounding may still have influenced these findings, with reference to environmental risk factors such as cadmium (68)(69)(70), pesticides (71)(72)(73) or air pollution (74)(75)(76)(77). Moreover, food frequency questionnaires used for acrylamide intake estimation in the included studies did not generally collect information about cooking methods, potentially affecting the reliability of exposure assessment (78) and contributing to heterogeneity in results.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we accounted for major established or putative risk factors such as body weight, smoking habits, hormone replacement therapy/oral contraceptive use, and partially lack of physical activity, and alcohol intake (64-67) by using the most adjusted estimates from included studies. However, we acknowledge that unmeasured confounding may still have influenced these findings, with reference to environmental risk factors such as cadmium (68)(69)(70), pesticides (71)(72)(73) or air pollution (74)(75)(76)(77). Moreover, food frequency questionnaires used for acrylamide intake estimation in the included studies did not generally collect information about cooking methods, potentially affecting the reliability of exposure assessment (78) and contributing to heterogeneity in results.…”
Section: Discussionmentioning
confidence: 99%
“…Most [153155, 159, 162, 163], but not all [158, 164], epidemiologic studies of postmenopausal women or all ages combined show risk estimates in the 0.73 to 1.01 range (Table 2). Two studies show greater risk associated with cadmium exposure for premenopausal women than for postmenopausal women [156, 165], whereas two other studies show the reverse [157, 166], with additional studies describing generally null associations for both groups [160, 161, 167, 168]. Stratification by estrogen receptor status does not reveal a consistent pattern.…”
Section: Introductionmentioning
confidence: 99%
“…This heavy metal is characterized by strong cumulative properties, and thus its content in the body increases with the duration of exposure and may be a cause of damage to various organs and systems [3,14]. Recent epidemiological studies provide more and more evidence that environmental exposure to this xenobiotic, nowadays occurring in economically developed countries, creates a threat to the health of the general population, mainly including a risk of damage to the kidney, liver, cardiovascular system, and skeleton, as well as the development of cancer and the deterioration of cognitive functions such as hearing and vision [3,9,13,[15][16][17][18]. It has been revealed that numerous effects of toxic action of cadmium, including the damaging impact on the organs of the oral cavity, result from its pro-oxidative properties [5,14,[19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Because current environmental exposure to cadmium creates a threat to the health of the general population [3,8,10,11,13,[15][16][17][18] and the lifetime human exposure to this xenobiotic will increase [9][10][11], the attention of researchers in recent years has been focused on finding effective ways to prevent the unfavourable health effects of exposure to this heavy metal. Taking into account the strong pro-oxidative properties of cadmium and the involvement of oxidative stress in the mechanisms of its damaging impact on various organs and systems [3,5,14,[19][20][21][22][23], the greatest interest among the possible protective agents has been paid to natural products characterized by strong antioxidative properties, including polyphenol-rich ones [14,[24][25][26].…”
Section: Introductionmentioning
confidence: 99%